2020
DOI: 10.1007/jhep09(2020)110
|View full text |Cite
|
Sign up to set email alerts
|

Brane-jet stability of non-supersymmetric AdS vacua

Abstract: We classify the non-supersymmetric, and perturbatively stable within D = 4, AdS vacua of maximal D = 4 supergravity with a dyonic ISO(7) gauging in a large sector of the supergravity. Seven such vacua are established within this sector, all of them giving rise to non-supersymmetric AdS4× S6 type IIA backgrounds with and without non-trivial warpings and with internal fluxes. Then, we analyse the dynamics of various probe Dp- branes in these backgrounds searching for potential brane-jet instabilities. In all the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…Namely, that the relevant AdS solutions have an associated consistent truncation to lower-dimensional maximal gauged supergravity, and that the internal space in the ordinary D = 10 or D = 11 sense, must be topologically spherical. These are not severe limitations, since the class of AdS solutions of this type still comes in cornucopious abundance [24][25][26][27]. Furthermore, having fixed an allowed lower-dimensional gauging, the same set of spherical harmonics on the associated round sphere is valid to compute the KK spectra about any other AdS solution that uplifts from the same gauging, even if the round sphere is not a (supersymmetric) solution itself.…”
Section: Jhep04(2021)283mentioning
confidence: 99%
“…Namely, that the relevant AdS solutions have an associated consistent truncation to lower-dimensional maximal gauged supergravity, and that the internal space in the ordinary D = 10 or D = 11 sense, must be topologically spherical. These are not severe limitations, since the class of AdS solutions of this type still comes in cornucopious abundance [24][25][26][27]. Furthermore, having fixed an allowed lower-dimensional gauging, the same set of spherical harmonics on the associated round sphere is valid to compute the KK spectra about any other AdS solution that uplifts from the same gauging, even if the round sphere is not a (supersymmetric) solution itself.…”
Section: Jhep04(2021)283mentioning
confidence: 99%
“…Now we study the worldvolume action of the M5-branes which is given by a sum of DBI and WZ terms. If the probe branes move slowly, the worldvolume action is 13) whereC (6) is the pull-back of the six-form potential. 8 Then the worldvolume action reduces to 14) where the kinetic and the potential terms are…”
Section: Jhep10(2020)010mentioning
confidence: 99%
“…In [8], the authors showed the only known perturbatively stable non-supersymmetric AdS 4 vacuum, [9,10], among the AdS vacua of four-, [11], and five-, [12], dimensional maximal gauged supergravity is, in fact, brane-jet unstable. See also [13] for the brane-jet stability from the D2-brane theories.…”
Section: Introduction and Conclusionmentioning
confidence: 99%
“…2 One may call this 'Absolute non-SUSY AdS Conjecture'. In such a strong formulation this conjecture is in conflict with the constructions of [46,[48][49][50][51]. 3 It then remains an interesting question whether some softened form of such a conjecture has a chance of being true.…”
Section: Jhep03(2021)284mentioning
confidence: 99%
“…as a cosmologically created bubble. 3 The recent discussions of [50,51] (based on [52]) suggest that their solutions are stable. However, it is not clear to us to which extent non-perturbative instabilities can be excluded.…”
Section: Jhep03(2021)284mentioning
confidence: 99%